PENGEMBANGAN WEBSITE E-RESELLER PT XYZ MENGGUNAKAN FRAMEWORK CODE IGNITER - ARIFUDDIN, ALY MULKAN; RAKHMAT, GALIH ASHARI (e-Proceeding FTI, 2024)
In the current era of globalization, advances in science and technology play an important role in people's lives. The significant influence of this progress can be seen in the use of websites as tools that simplify various aspects of human work. Entrepreneurs, especially in large companies, are increasingly paying attention to the importance of websites as an effective means for promotion, sales and providing company information. PT XYZ, as one of the companies that understands the strategic value of websites, has adopted digital platforms, especially in developing E-Reseller websites. With a focus on the IT & Digital Innovation division, this company actively utilizes the Code Igniter framework to ensure fast, simple and efficient website development. Through this research, the author discusses the development of a new menu on the E-Reseller website, exploring development steps using the PHP programming language, the Code Igniter framework, and other supporting technologies such as HTML, CSS, and JavaScript with the Bootstrap framework. This practical work report entitled "Development of the PT XYZ E-RESELLER Website" discusses the problem of developing a new menu and sets the goal of understanding the method for developing an E-Reseller website. By using various technologies such as PHP, Code Igniter, HTML, CSS, and JavaScript, along with supporting tools such as Visual Studio Code, Tortoise SVN, and MariaDB, PT XYZ continues to innovate in improving its services and operational efficiency through its E-Reseller website. under development. Abstrak Dalam era globalisasi saat ini, kemajuan ilmu pengetahuan dan teknologi memainkan peran penting dalam kehidupan masyarakat. Pengaruh signifikan dari kemajuan tersebut terlihat dalam penggunaan website sebagai alat yang mempermudah berbagai aspek pekerjaan manusia. Para pengusaha, terutama di perusahaan besar, semakin memperhatikan pentingnya keberadaan website sebagai sarana efektif untuk promosi, penjualan, dan penyediaan informasi perusahaan. PT XYZ, sebagai salah satu perusahaan yang memahami nilai strategis website, telah mengadopsi platform digital, khususnya dalam pengembangan website E-Reseller. Dengan fokus pada divisi IT & Digital Innovation, perusahaan ini aktif memanfaatkan framework Code Igniter untuk memastikan pengembangan website yang cepat, sederhana, dan efisien. Melalui penelitian ini, penulis membahas tentang pengembangan menu baru pada website E-Reseller, mengeksplorasi langkah-langkah pengembangan dengan menggunakan bahasa pemrograman PHP, framework Code Igniter, dan teknologi pendukung lainnya seperti HTML, CSS, dan JavaScript dengan framework Bootstrap. Laporan kerja praktik ini berjudul "Pengembangan Website E-RESELLER PT XYZ" membahas permasalahan pengembangan menu baru dan menetapkan tujuan untuk memahami metode pengembangan website E-Reseller. Dengan menggunakan berbagai teknologi seperti PHP, Code Igniter, HTML, CSS, dan JavaScript, bersama dengan alat pendukung seperti Visual Studio Code, Tortoise SVN, dan MariaDB, PT XYZ terus berinovasi dalam meningkatkan layanan dan efisiensi operasionalnya melalui website E-Reseller yang sedang dikembangkan.